Pengembangan Strategi Pemasaran 4C sebagai Upaya Meningkatkan Kunjungan Pasien ke Poli OBGYN Rumah Sakit Tingkat IV Samarinda - Fitriasari, Nur; Wahyudi, Bayu; Sukajie, Bambang; Widjaja, Yani Restiani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This study aims to analyze the implementation of the 4C marketing strategy—Co-creation, Currency, Communal Activation, and Conversation—in increasing patient visits, particularly among pregnant women covered by the BPJS national health insurance program, to the Obgyn Clinic at Level IV Hospital Samarinda through 4D ultrasound services. These services are positioned as a flagship offering, providing vivid fetal imaging experiences at no additional cost, thereby enhancing the hospital's appeal amidst competition in health services. The research employed a descriptive qualitative approach, with data collected through structured interviews involving hospital management, medical personnel, and patients. It was further supported by quantitative data obtained from questionnaires distributed to 40 pregnant patients. The findings indicate that the Co-creation dimension fosters active patient participation through direct communication and engagement in interpreting ultrasound results. The Currency dimension was perceived very positively, as patients felt they received high-value services without extra charges. Communal Activation strategies through health cadres, social media, and maternal support groups were effective in raising awareness and interest in the 4D ultrasound services. Meanwhile, the Conversation dimension, encompassing both face-to-face and digital interactions, played a vital role in building trust and long-term patient loyalty. Based on these findings, the 4C marketing strategy has proven to be relevant and effective when implemented in National Health Insurance-based hospital services, with an increasing trend in average patient visits from 180 patients per month to 220 patients per month (a 22% increase). This study recommends the use of mixed methods in future research to obtain a more complete understanding of how each dimension influences patient visitation behavior.